Seaweed-Based Blue Carbon Development in Indonesia: Feasibility and Policy Framework for a Community-Based Pilot in West Nusa Tenggara, Indonesia - Supiandi; Kartika Listriana; Dyah Erowati; Suharyanto; Didit Eko Prasetiyo; Muhammad Husnul Aini; Akmal Fathu Rohman (Yayasan Ghalih Pelopor Pendidikan, 2026)
This paper reviews the scientific and regulatory basis for seaweed-based blue carbon development in Indonesia, evaluates the technical and economic feasibility of a proposed pilot project in Seriwe, East Lombok, West Nusa Tenggara, and develops a policy and institutional framework for community-based implementation. Using a mixed-method design that combines a narrative literature review, regulatory document analysis, oceanographic site-suitability assessment, and techno-economic feasibility analysis, the study finds that deep-water storage of cultivated seaweed biomass at depths exceeding 1,000 metres is technically feasible at the study site and yields a preliminary benefit-cost ratio of 1.10, with an estimated net benefit of approximately IDR 16.7 million per hectare. The proposed 4-hectare pilot, developed in partnership with PT Arbon Earth Indonesia, local seaweed farmer groups, and Koperasi Desa Merah Putih, is designed to integrate with Indonesia's national carbon economic value (Nilai Ekonomi Karbon) system under Presidential Regulation No. 110/2025.